Thermoformed occlusal splints for the treatment of masticatory muscle pain: a clinical trial - De Nordenflycht, Diego; Salinas, Javier; Armstrong, Lisa (Brazilian Dental Science, 2022)
Objective: Compare the clinical effectiveness of custom thermoformed occlusal splints (OS) alongside behavioraland self-care therapy (BST) in the management of myalgia of the masticatory muscles. Material and methods:A controlled clinical trial was conducted with a total of 46 subjects with a diagnosis of myalgia according tothe Diagnostic Criteria for Temporomandibular Disorders (DC/TMD). All subjects were treated with BST at thebeginning of the study and were then randomized into four groups: behavioral and self-care control group;Thermoformed Tough-elastic splint group; Thermoformed Soft-elastic splint group, and non-occlusive splintgroup. Follow-ups were carried out at 2, 6, and 10 weeks, where it was evaluated: pain in the masticatorymuscles, mandibular range of motion, mandibular functional limitation, and occlusal discomfort. Data wereanalyzed with Doornik and Hansen, Shapiro–Wilk, and ANOVA at p=0.05. Results: All the variables showedsignificant improvement (p0.05), while the Thermoformed Tough-elastic splintwas the most efficient in terms of the mandibular functional limitation. The occlusal discomfort decreased overtime, but without statistically significant differences in terms of time and design of OS. Conclusion: The additionof thermoformed OS to behavioral and self-care therapy does not have a significant impact on myalgia of themasticatory muscles.KEYWORDSMyalgia; Occlusal splint; Self-care; Temporomandibular joint disorders; Thermoformed splint.